2014
DOI: 10.1007/s12298-014-0222-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mevinolin on chloroplast terpenoids in Cannabis sativa

Abstract: Plants synthesize a myriad of isoprenoid products that are required both for essential constitutive processes and for adaptive responses to the environment. Two independent pathways for the biosynthesis of isoprenoid precursors coexist within the plant cell: the cytosolic mevalonic acid (MVA) pathway and the plastidial methylerythritol phosphate (MEP) pathway. In this study, we investigated the inhibitory effect of the MVA pathway on isoprenoid biosynthesized by the MEP pathway in Cannabis sativa by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This conclusion is consistent with the biochemical properties of GFDPS, which was found to use GGDP as its preferred allylic cosubstrate; GGDP is also formed in plastids (Hemmerlin et al, 2012). The increase in sesterterpenoid accumulation upon MEV treatment has a precedent in previous studies that have shown how blocking one terpenoid biosynthetic pathway stimulates increases in terpenoid levels by the other pathway (Laule et al, 2003;Ramak et al, 2013;Mansouri and Salari, 2014). Despite the formation of L. canum sesterterpenoids from MEP pathway substrates, the GT transcriptome of this species contains sequences for nearly all steps of both the MEP and MVA pathways.…”
Section: Gfdp Synthase Is Localized To the Plastids Of Gt Cells And Usupporting
confidence: 87%
“…This conclusion is consistent with the biochemical properties of GFDPS, which was found to use GGDP as its preferred allylic cosubstrate; GGDP is also formed in plastids (Hemmerlin et al, 2012). The increase in sesterterpenoid accumulation upon MEV treatment has a precedent in previous studies that have shown how blocking one terpenoid biosynthetic pathway stimulates increases in terpenoid levels by the other pathway (Laule et al, 2003;Ramak et al, 2013;Mansouri and Salari, 2014). Despite the formation of L. canum sesterterpenoids from MEP pathway substrates, the GT transcriptome of this species contains sequences for nearly all steps of both the MEP and MVA pathways.…”
Section: Gfdp Synthase Is Localized To the Plastids Of Gt Cells And Usupporting
confidence: 87%
“…Several studies, cataloged in Table 1, have tested the role of biotic and abiotic elicitors on the effects of cannabinoid biosynthesis, revealing the sensitivity of this pathway to external signals. In contrast, studies conducted by Mansouri et al (2009a,b, 2011, 2013 and 2016), Mansouri and Asrar (2012), Mansouri and Rohani (2014) and Mansouri and Salari (2014) demonstrated that abscisic acid, cycocel, ethephon, gibberellic acid, and mevinolin can all alter cannabinoid biosynthesis. While Flores-Sanchez et al (2009) tested a large number of elicitors for effects on cannabis hairy root cell cultures, this did not induce cannabinoid biosynthesis.…”
Section: Discussionmentioning
confidence: 86%
“…The precise role of cannabinoid in plant defence is not yet known. The plant growth regulators, including ABA, cycocel, ethephon, GAs, salicylic acid, γ-Aminobutyric acid (GABA), and mevinolin can manipulate cannabinoid biosynthesis and modulating secondary cannabis metabolites [22,[118][119][120][121].…”
Section: Possible Modulation Of Cannabis Secondary Metabolite By Endomentioning
confidence: 99%